Iceland - Thordarson, Thor; Höskuldsson, Ármann (Classic geology in Europe ;, 2022)
For over a decade this concise and authoritative field guide to an exceptional natural laboratory has been an essential companion for all those visiting Iceland to observe the Earth in action.